Tangled roots : the Appalachian Trail and American environmental politics - Mittlefehldt, Sarah (Weyerhaeuser environmental book., 2013)
"The Appalachian Trail, a thin ribbon of wilderness running through the densely populated eastern United States, offers a refuge from modern society and a place apart from human ideas and institutions. But as environmental historian and thru-hiker Sarah Mittlefehldt argues, the trail is also a conduit for community engagement and a model for public-private cooperation and environmental stewardship.In Tangled Roots, Mittlefehldt tells the story of the trail's creation. The project was one of the first in which the National Park Service attempted to create public wilderness space within heavily populated, privately owned lands. Originally a regional grassroots endeavor, under federal leadership the trail project retained unprecedented levels of community involvement. As citizen volunteers came together and entered into conversation with the National Parks Service, boundaries between "local" and "nonlocal," "public" and "private," "amateur" and "expert" frequently broke down. Today, as Mittlefehldt tells us, the Appalachian Trail remains an unusual hybrid of public and private efforts and an inspiring success story of environmental protection. Sarah Mittlefehldt is assistant professor of environmental studies at Green Mountain College."Tangled Roots makes a contribution to the literature of environmental conservation history that is as unusual as the trail itself. In a gentle, approachable, and engaging style it tells the history of one of the most important and beloved conservation initiatives in American history and at the same time comments on a wide range of subjects in ways that are both insightful and fresh." --James Feldman, author of A Storied Wilderness"Tangled Roots will find readership among environmental and forest historians and will end up on the Christmas lists and in the backpacks of the trail's many fans. It is original and well-researched, ranging the length of the trail and lingering in one or another spot to explore representative or illuminating developments." --Kathryn Newfont, author of Blue Ridge Commons"This superb history of the construction and management of the Appalachian Trail not only narrates the creation of the most famous long-distance hiking trail in modern America; it also offers a cautionary tale about the changing roles of private landowners, volunteer hiking enthusiasts, land managers, and federal agencies in the oversight of that trail. In so doing, Sarah Mittlefehldt beautifully illustrates the changing environmental politics of the twentieth century in a book whose implications extend far beyond the AT." --William Cronon"--